2017
DOI: 10.1016/j.visres.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Acircularity index and axis ratio of the foveal avascular zone in diabetic eyes and healthy controls measured by optical coherence tomography angiography

Abstract: Given the complexity of the current system used to stage diabetic retinopathy (DR) and the risks and limitations associated with intravenous fluorescein angiography (IVFA), noninvasive quantification of DR severity is desirable. We examined the utility of acircularity index and axis ratio of the foveal avascular zone (FAZ), metrics that can noninvasively quantify the severity of diabetic retinopathy without the need for axial length to correct for individual retinal magnification. A retrospective review was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
168
1
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(196 citation statements)
references
References 63 publications
20
168
1
7
Order By: Relevance
“…After controlling for confounding factors, we found that parafoveal vessel density and FAZ circularity index were independently related to mGCIPL thinning in the present study (table 3). Similarly, previous studies have suggested that changes in the FAZ circularity index13 and parafoveal vessel density12 are more reliably correlated with microcirculation impairment in DR. FAZ size shows high variability in healthy eyes, and it is affected by individual differences in ocular magnification such as variation in axial length 21. To our knowledge, this is the first study to report the relationship between changes of OCTA-derived microvascular parameters and mGCIPL thickness in patients with T2DM.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…After controlling for confounding factors, we found that parafoveal vessel density and FAZ circularity index were independently related to mGCIPL thinning in the present study (table 3). Similarly, previous studies have suggested that changes in the FAZ circularity index13 and parafoveal vessel density12 are more reliably correlated with microcirculation impairment in DR. FAZ size shows high variability in healthy eyes, and it is affected by individual differences in ocular magnification such as variation in axial length 21. To our knowledge, this is the first study to report the relationship between changes of OCTA-derived microvascular parameters and mGCIPL thickness in patients with T2DM.…”
Section: Discussionsupporting
confidence: 61%
“…The FAZ area is enlarged in both DR and retinal vein occlusion due to destruction of the vascular arcades 7 11. Prior studies have qualitatively demonstrated that the FAZ becomes more a circular in DR, with effects on the FAZ perimeter and circularity index 13. Thus, loss of FAZ circularity is a good indicator of vascular dropout, and is associated with disease progression in vascular maculopathy 15.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, another group reported increased fractal dimension in both vascular layers of patients with NPDR compared to control subjects [23]. In patients with PDR, significant FAZ area enlargement and a decrease of FAZ circularity and vessel density was detected in both superficial and deep vascular layers [28]. …”
Section: Octa Parameters In the Superficial Deep And/or Intermediatmentioning
confidence: 99%
“…Capillary closure may occur in early stages of DR, worsening as DR progresses; thus measurements such as FAZ size could potentially represent biomarkers for DR progression . Krawitz et al found a strong correlation between acircularity of the FAZ and the presence of DR.…”
Section: Diabetic Retinopathy (Dr)mentioning
confidence: 99%